Correlation Between Anemia, Sexually Transmitted Infections, and Low Birth Weight Among Pregnant Women - Suprapto, Elviara Martha Tinova; Putra, Mega Memory Rahasa; Bangun, Thomas Yan; Azizah, Nur (Majalah Kedokteran Bandung, 2025)
Anemia in pregnancy and sexually transmitted infections (STIs) are global health issues linked to low birth weight. This study explored the correlation between these factors and low birth weight at the General Hospital of Scholoo Keyen, South Sorong, Southwest Papua, Indonesia. A cross-sectional observational analytic study was conducted from September 2022 to March 2023, involving pregnant women who gave birth at the General Hospital of Scholoo Keyen. The correlation between risk factors and low birth weight was analyzed using the chi-square test with a significance threshold of p<0.05. Results showed that among 162 pregnant women (average age: 27.72±6.62 years), anemia severity was distributed as follows:severe (3.7%), moderate (16.0%), and mild (40.1%). However, no significant relationship was found between anemia and birth weight (p=0.850, p>0.05). The incidences of HIV, syphilis, and hepatitis B were 3.1%, 13.6%, and 7.4%, respectively. A significant association was identified between HIV infection and low birth weight (p=0.000), while no such association was found for syphilis (p=0.160) or hepatitis B infection (p=0.852). In conclusion, HIV infection is associated with low-birth-weight newborns, but there are no apparent relationships between anemia, syphilis, or hepatitis B infection and low-birth-weight newborns, This study implies the importance of nutritional support among pregnant mothers with HIV and delaying pregnancy in HIV-positive women to until their immune system improve.